Smart marketing with the internet of things - Simoes, Dora, 1970-; Barbosa, Belem, 1971-; Filipe, Sandra, 1973- (Hershey, PA : IGI Global, Business Science Reference, 2019)
'This book provides knowledge and skills that marketers need to act in the internet of things era. It focuses on the implications of the internet of things on marketing and provides cues on how to deal with its opportunities and challenges'--
Includes bibliographical references : pages 265-296 and index.
Keywords: Internet marketing